Kualitas Pelayanan Pada Pos Kesehatan Desa (Poskesdes) Kecamatan Aertembaga Kota Bitung - Dipan, Rolien (JURNAL ILMIAH SOCIETY, 2016)
Efforts to improve health services in the community in the form of village health post (Poskesdes) which is a village health efforts Community Based (UKBM) were established in the village in order to suppress / provide basic services for rural communities. Writing is to know the quality of service to the village health posts in the district Aertembaga Bitung City. The research method uses a qualitative approach, with data collection techniques, free interviews, observation and documents. Conclusions from the study showed that the quality of service in the district Poskesdes Aertembaga not optimal. Limited human resources managers, and health care activities in implementation has not been fully guided as technical guidelines applicable government regulations. Means of supporting the majority considered inadequate. The supervisory system of the upper level of the service activity has not been smooth